The conservation of the mosaic of the House of the Ionic Capitals in Hierapolis (Pamukkale, Turkey) - Uguryol, Mehmet (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2013)
This paper describes the conservation of a figurative and geometrical patterned 5th century A. D. mosaic in the ruins of the House of the Ionic Capitals in Hierapolis, which is one of the world heritage sites. The mosaic had significant quantity of detached and disintegrated tesserae as a result of deterioration of its bedding layer. The conservation process included fixing detached tesserae by reinforcing the bedding layer with lime mortars; integrating disintegrated original tesserae to fill the small lacunae for a better visual perception; mechanical and poultice cleaning; using permeable geotextile in reburial against environmental factors, and herbicide application to prevent plant intrusion. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: Mosaic conservation; Mosaic restoration; Consolidation; Lime mortar; Tesserae; Hierapolis; Archaeology; Art; Chemistry; Geology; Materials Science; Spectroscopy